Welfare assessment of broiler chickens at live bird market of Chattogram in Bangladesh. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to assess the welfare conditions of broiler chickens in the live bird markets (LBMs) in Bangladesh. Materials and Methods: A total of fifty broiler outlets were studied in 10 LBMs of Chattogram, Bangladesh. A total of 10 chickens were observed to check the welfare issues during slaughter from each outlet (N = 500). The data were collected using a structured questionnaire method through interviews of the vendors and observation of the lairage and slaughter practice. Results: The study revealed that the stocking density was significantly higher in cage-type lairage than in floor-type (p < 0.05). The feeding and drinking areas for the chickens were significantly but negatively correlated to the stocking density. The duration between unloading of broiler chickens at LBMs and feeding or drinking could exceed 5 hours in 22% of outlets. The mortality was significantly higher in the bigger outlets than the smaller outlets (p < 0.05). During pre-slaughter handling, the one-wing grasping method was practiced more in the bigger outlets (p < 0.05) whereas the feet grasping method was used more in the smaller outlets (p < 0.05). Moreover, the knives used to slaughter the chickens were not sharpened daily in 76% of outlets. Conclusion: This study indicated that the broiler chickens in the LBMs of Chattogram had to face many stress episodes at different stages at their penultimate moments—from lairage to slaughter—which led to poor welfare conditions and exacerbated the suffering of chickens.J. Adv. Vet. Anim. Res., 11(3): 803-809, September 2024http://doi.org/10.5455/javar.2024.k832